ANALISIS DAN INTEPRETASI LAGU “GRAVITY“ KARYA JOHN MAYER - Mohamad Syafei (Saraswati)
This study discusses the song interpretation of John Mayer’s work, the Gravity. The Mayer’s Gravity was performed as a part of the author’s academic final task recital in pop-jazz studies. Research method that is utilized in this study is the musicological method with performance interpretation approach that encompass practicing, performance, music analysis, and interpretation of the song lyric. This study concludes that the song is structured by a simple three part song form (AABA), and the lyric does not express a literal meaning but more symbolic with multiple understanding.   Keywords: Gravity, analysis, interpretation, Mayer.